An Integration Study of MANET and VANET for Communication in Smart Cities - Ajeng Mayang; Yudi Barnadi; Ase Suryana (Yayasan Cita Cendekiawan Al Khwarizmi, 2025)
The development of Internet of Things (IoT) technology has accelerated the development of Smart City, where efficient and real-time communication infrastructure is considered a very important aspect here. Mobile Ad-hoc Networks (MANETs) and Vehicular Ad-hoc Networks (VANETs) topologies offer flexible and adaptive communication models that can respond to dynamic mobility for changes in topology conditions. Generally MANETs are used for pedestrians and stationary sensors, while VANETs are used for vehicles. This study will use both topologies to be simulated for their use if applied in the development of smart cities. In this study, the feasibility and reliability of both topologies, both MANET and VANET will be tested by evaluating performance in terms of Packet Delivery Ratio (PDR) for data transmission reliability, delay (latency) for information timeliness, and throughput for data transfer capacity, which is done using NS-3 as its simulator. The number of nodes used varies from 10 - 100 for each MANET and VANET topology. Simulation results consistently show that networks using both topologies can provide superior performance. The results of this research show that combining the strengths of MANET and VANET is very suitable for future smart city applications. With its ability to provide reliable and efficient communications in highly dynamic urban environments, this technology is one of the promising solutions for building a robust and responsive communication system.